Larangan Tinggal Serumah bagi Suami Istri Sebelum Walimatul ‘Urs dalam Perspektif Hukum Islam: Antara Ketentuan Syariah dan Dominasi Adat - Azkia, Nurul (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2025)
The practice of prohibiting married couples from living together after the marriage contract but before the walīmat al-‘ursy (commonly known as nikah gantung) remains socially binding in Hamayung Village, Hulu Sungai Selatan. This practice has generated controversy because it delays the exercise of spousal rights and obligations that, under Islamic law, should take effect immediately upon the conclusion of the marriage contract. As such, nikah gantung reflects a tension between the legal certainty of Islamic law and the dominance of customary norms as living law. This study aims to assess the compatibility of nikah gantung with Islamic legal principles through the frameworks of ‘urf and maqāṣid al-sharī‘ah. The research adopts a normative Islamic legal (juridical-fiqhiyyah) method combined with a socio-legal approach, drawing on classical and contemporary fiqh literature, usul al-fiqh sources, statutory regulations, and limited field data to contextualize the practice. Data are analyzed qualitatively through takyīf fiqhī, evaluation of ‘urf, and maqāṣid-based assessment. The findings indicate that postponement of post-contractual rights may be permissible when it is voluntary and grounded in legitimate shar‘i excuses; however, the practice in Hamayung Village is collective, coercive, and reinforced by social sanctions, effectively transforming the recommended walīmat al-‘ursy into a de facto legal condition. Consequently, this practice cannot be classified as ‘urf ṣaḥīḥ and contradicts legal certainty and family welfare. The study recommends strengthening legal awareness and repositioning customary norms to align with the objectives of Islamic law.